2018
DOI: 10.22175/mmb2017.10.0052
|View full text |Cite
|
Sign up to set email alerts
|

Marbling Texture’s Effects on Beef Palatability

Abstract: Abstract:The objective of this study was to evaluate the effects of marbling texture on consumer and trained sensory panel ratings of beef strip loin steaks from 3 USDA quality grades. Beef strip loins (n = 117) were selected from 3 quality grades [Top Choice (Modest 00 -Moderate 100 marbling), Low Choice (Small 00 -Small 100 marbling), and Select (Slight 00 -Slight 100 marbling)] to equally represent three different marbling texture groups: fine, medium, and coarse, via visual appraisal. There were no quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
(6 reference statements)
4
22
2
Order By: Relevance
“…In contrast to the current finding, Lee et al (2019) reported no differences in flavor scores for 1 ++ grade Hanwoo beef samples between coarse and fine marbling groups. Conversely, a study by Vierck et al (2018) showed that coarsely-marbled steaks exhibited higher scores for flavor and juiciness compared to finely-marbled steaks in the USDA choice beef grade. Regarding the tenderness and juiciness, the panelists reported no differences in their scores between the two marbling groups (p>0.05).…”
Section: Resultsmentioning
confidence: 95%
“…In contrast to the current finding, Lee et al (2019) reported no differences in flavor scores for 1 ++ grade Hanwoo beef samples between coarse and fine marbling groups. Conversely, a study by Vierck et al (2018) showed that coarsely-marbled steaks exhibited higher scores for flavor and juiciness compared to finely-marbled steaks in the USDA choice beef grade. Regarding the tenderness and juiciness, the panelists reported no differences in their scores between the two marbling groups (p>0.05).…”
Section: Resultsmentioning
confidence: 95%
“…Sensory panelists were trained according to the American Meat Science Association (AMSA) Sensory Guidelines (AMSA, 2016). Panelists were trained at 15 training sessions 2 wk prior to panels, using anchors and methods similar to those described by Lucherk et al (2016) and Vierck et al (2018). Similar to consumer sensory panelists, trained sensory panelists evaluated samples in individual sensory booths under low intensity (<107.64 lumens) red incandescent lighting.…”
Section: Trained Sensory Panelsmentioning
confidence: 99%
“…Sensory analyses were conducted according to the procedures outlined in the AMSA Research Guidelines for Cookery, Sensory Evaluation, and Instrumental Tenderness Measurements of Meat ( AMSA, 2015 ), with training and anchors similar to those described by Lucherk et al (2016) and Vierck et al (2018) . Twenty-four hours prior to cooking, steaks were thawed on trays at 2.7 ± 0.9 °C.…”
Section: Methodsmentioning
confidence: 99%